The importance of the standards' knowledge in the teaching of English at the fiscal urban morning elementary schools in Riobamba in the School year 2006 - 2007 - Cabezas Árevalo, Leonardo Efraín (2007)
The purpose of the present study was to investigate "The importance of the standards' knowledge in the teaching of English at the fiscal urban morning elementary schools in Riobamba in the school year 2006 - 2007". Their ability, attitude toward EFL standards, and the view of integrating standards into classroom teachers. Participants completed a survey that addressed: fulfils professional responsibilities established by the school district, competence to content knowledge appropriate to the teaching position, competence in planning and preparing for instruction, competence in classroom management, use a variety of methods to monitor student learning, and their opinion about standards for EFL classes results indicated that both directors and english teachers did not have knowledge about standards in teaching English, and have no information about standards from the different levels of educational departments. Classroom teachers did not show a consistent knowledge about standards when evaluating the importance of using standards at elementary schools.